2006
DOI: 10.1038/sj.eye.6702563
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of macular function by microperimetry in unilateral resolved central serous chorioretinopathy

Abstract: Purpose To determine macular sensitivity and fixation characteristics in patients with unilateral resolved central serous chorioretinopathy (CSC) using fundus-related microperimetry. Methods We reviewed 15 eyes with resolved CSC and 15 normal healthy eyes that had undergone fundus-related microperimetry. The macular sensitivity was measured using the recently introduced fundus-related microperimeter, MP-1. The best-corrected visual acuity (VA) (BCVA), mean retinal sensitivity in the central 101 (central microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 15 publications
2
66
0
1
Order By: Relevance
“…13,14 The usefulness of microperimetry (MP) in evaluating retinal sensitivity (RS) and central retinal field function is well known in resolved CSC. [15][16][17][18][19][20][21][22][23][24] Although most MP evaluations of RS in patients after CSC resolution have used the MP-1 Microperimeter (Nidek Technologies, Padova, Italy), [15][16][17][18][19][20][21][22][23][24] this microperimeter presents MP values on a confocal scanning laser ophthalmoscope (cSLO) image without producing an optical coherence tomography (OCT) image. Therefore, direct comparisons between RS and retinal changes at a corresponding point are not possible.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The usefulness of microperimetry (MP) in evaluating retinal sensitivity (RS) and central retinal field function is well known in resolved CSC. [15][16][17][18][19][20][21][22][23][24] Although most MP evaluations of RS in patients after CSC resolution have used the MP-1 Microperimeter (Nidek Technologies, Padova, Italy), [15][16][17][18][19][20][21][22][23][24] this microperimeter presents MP values on a confocal scanning laser ophthalmoscope (cSLO) image without producing an optical coherence tomography (OCT) image. Therefore, direct comparisons between RS and retinal changes at a corresponding point are not possible.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with microperimetry in eyes with CSC show significantly lower RS not only at the central but also in the paracentral area of the macula [29][30][31][32]. Furthermore, Ozdemir et al [33] found that eyes with resolved CSC had a statistically significant reduced central RS compared with controls. Although many studies have shown improvement in visual function after PDT [29][30][31][32], the improvement in BCVA may not be accompanied by an improvement in central RS.…”
Section: Discussionmentioning
confidence: 95%
“…Evaluation of location and stability of fixation by MP-1 was previously reported in some macular diseases such as age-related macular degeneration and central serous retinopathy. 6,11 Previous studies have shown that fixation stability was significantly decreased in diabetic patients compared with control subjects, particularly in eyes with CSME. 7,9 Kube et al 9 detected that fixation stability was significantly decreased in diabetic patients in comparison to control with scanning laser ophthalmoscopy (SLO).…”
Section: Discussionmentioning
confidence: 99%